Tea Waste Products: A New Low-Cost and Green Adsorbent Alternative for Rhodamine-B Dye Removal - Meyliana Wulandari; Syed Azhar Syed Sulaiman; Nofrizal Syamsudin (Universitas Gadjah Mada, 2022)
Tea waste products were thrown out without any intention to utilize their potential benefits. This waste will help to improve industries to absorb rhodamine-B (RhB) dye pollutants currently used by various industries. This study evaluated the application of tea waste products to remove Rh-B from aqueous systems by investigating adsorption kinetics in a batch process. The ability and mechanism of Indonesian black and green tea in RhB adsorption were determined by optimizing temperature, pH, contact time, and concentration of dye solution. Achievement of equilibrium attained at 40 min for black tea (BT) and green tea (GT). Subsequently, the adsorption capacity reached optimum at 80 and 70 °C for GT, and the maximum adsorption capacities for BT and GT were 22 and 47 mg/g, respectively, at pH 2.5. The absorption of RhB in both bio-sorbents was an exothermic process that well fit the Langmuir model and a pseudo-second-order reaction. The presented R2 values from the Langmuir isotherm are 0.9967 (BT) and 0.9979 (GT). The separation factor was determined as 0.026 (BT) and 0.055 (GT). Thermodynamic studies were carried out to calculate free energy, enthalpy, and entropy changes. The result showed that the removal study of BT and GT is 59.06 and 60.25%, respectively, using 10% acetic acid. Study comparisons were carried out on both teas with other bio-sorbents for more improvement. These results show that tea waste products can be used as alternative adsorbents to absorb RhB from wastewater.